Cholesterol mediates chitosan activity on phospholipid monolayers and Langmuir-Blodgett films - Pavinatto, Felippe J (Langmuir : the ACS journal of surfaces and colloids, 2009)
The polysaccharide chitosan has been largely used in many biological applications as a fat and cholesterol reducer, bactericide agent, and wound healing material. While the efficacy for some of such uses is proven, little is known about the molecular-level interactions involved in these applications. In this study, we employ mixed Langmuir and Langmuir-Blodgett (LB) films of negatively charged dimyristoyl phosphatidic acid (DMPA) and cholesterol as cell membrane models to investigate the role of cholesterol in the molecular-level action of chitosan. Chitosan does not remove cholesterol from the monolayer. The interaction with chitosan tends to expand the DMPA monolayer due to its interpenetration within the film. On the other hand, cholesterol induces condensation of the DMPA monolayer. The competing effects cause the surface pressure isotherms of mixed DMPA-cholesterol films on a chitosan subphase to be unaffected by the cholesterol mole fraction, due to distinct degrees of chitosan penetration into the film in the presence of cholesterol. By combining polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS) and sum-frequency generation spectroscopy (SFG), we showed that chitosan induces order into negatively charged phospholipid layers, whereas the opposite occurs for cholesterol. In conclusion, chitosan has its penetration in the film modulated by cholesterol, and electrostatic interactions with negatively charged phospholipids, such as DMPA, are crucial for the action of chitosan